2019
DOI: 10.1136/jech-2019-212191
|View full text |Cite
|
Sign up to set email alerts
|

Too sick to work, too healthy to qualify: a cross-country analysis of the effect of changes to disability benefits

Abstract: BackgroundDenmark and Sweden have implemented reforms that narrowed disability benefit eligibility criteria. Such reforms in combination with increasing work demands create a pincer movement where in particular those with moderate health problems might be unable to comply with work demands, but still not qualify for permanent disability benefits, ending up with temporary means-tested or no benefits. This paper examines whether this actually happened before and after the reforms.MethodsThe Survey of Health, Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Spending on social insurance, such as workers’ compensation and disability insurance, has been growing. In nations such as the USA, Australia, Denmark and Sweden, the share of the population receiving disability insurance benefits has grown in recent decades 10–12. Governments have responded by tightening eligibility criteria or reducing benefit generosity 13 14.…”
Section: Introductionmentioning
confidence: 99%
“…Spending on social insurance, such as workers’ compensation and disability insurance, has been growing. In nations such as the USA, Australia, Denmark and Sweden, the share of the population receiving disability insurance benefits has grown in recent decades 10–12. Governments have responded by tightening eligibility criteria or reducing benefit generosity 13 14.…”
Section: Introductionmentioning
confidence: 99%
“…Research studying employment, early retirement and disability pension in Sweden over this time period suggests that many with chronic illness were forced out of employment through alternative exit routes, due to eligibility restrictions of disability pension [39,40]. Taken together with the finding that women were more likely to obtain disability pension than men, our findings may suggest that comorbidity acted as a push factor of early retirement for men, forcing them into early retirement due to failures to qualify for disability pension.…”
Section: Policy Context and Implicationsmentioning
confidence: 56%
“…Similarly, since CMD only was not as strongly associated with disability pension as LLI only and LLI +CMD, but specifically associated with unemployment, it may suggest that those with CMD, in the absence of LLI, are less likely to qualify for disability pension and instead become unemployed [40,41]. This would mean that further restrictions to disability pension are unlikely to facilitate extended working lives; rather, those too unwell to work would exit through a different route instead [40]. To extend working lives, policies may instead focus on supporting older workers to stay in employment through tailored workplace adaptations to address the diversity of older workers' needs.…”
Section: Policy Context and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent panel study identi ed that people with disability had higher levels of depression and anxiety symptoms during periods in which they were receiving disability insurance bene ts than when they were not, after accounting for time-varying changes in disability severity [5]. Studies from the UK and northern Europe showed that restricting access to disability insurance bene ts contributed to growth in the number of people with signi cant health concerns enrolled in unemployment programs [6], and increased the burden of ill health in this population [6][7][8]. People with frequent attendance in primary healthcare settings are more likely to receive disability bene ts in future than non-attenders or those with infrequent attendance [9].…”
Section: Relationship Between Health Status and Social Assistancementioning
confidence: 99%